HAK DAN KEWAJIBAN SUAMI ISTRI DAN HARTA BERSAMA DALAM PERKAWINAN MENURUT UU NO. 1 TAHUN 1974 - Sumoked, Jeffrin Pratama (JURNAL MEDIA HUKUM DAN PERADILAN, 2019)
A marriage sometimes has several kinds of marital assets. According to Law No. 1 of 1974, namely property, assets and joint assets. The three marriages above, the inheritance of each husband / wife has the full right to carry out legal acts while the joint assets are assets obtained during the marriage of the husband or wife can act on the agreement of both parties. Furthermore, concerning joint assets, which are obtained by the wife / husband or only by the husband or wife, constitute joint income and joint responsibility